2016
DOI: 10.1093/icvts/ivw378
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bioprostheses anti-calcification treatment: comparative follow-up between Mitroflow LX and Magna pericardial xenografts using a propensity score-weighted analysis

Abstract: The P-Magna prosthesis showed significantly better overall and cardiac-related survival than the Mitroflow LX. The higher early SVD and reoperation rates seen with the Mitroflow LX prosthesis did not impact negatively on valve-related survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Furthermore, patients who received a MF valve were more likely to have a valve related cause of death. This is consistent with the findings of Blasco‐Lucas et al who reported that MF patients had a 44% increased hazard of death over a 4‐year period of follow‐up compared to patients receiving a comparator valve at their institution. While our study cannot demonstrate causation, the increased incidence of SVD associated with the MF aortic bioprosthesis is likely a contributing factor in the increased mortality rate as suggested by a large Veterans Affairs study which identified SVD to be a strong independent predictor of mortality.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, patients who received a MF valve were more likely to have a valve related cause of death. This is consistent with the findings of Blasco‐Lucas et al who reported that MF patients had a 44% increased hazard of death over a 4‐year period of follow‐up compared to patients receiving a comparator valve at their institution. While our study cannot demonstrate causation, the increased incidence of SVD associated with the MF aortic bioprosthesis is likely a contributing factor in the increased mortality rate as suggested by a large Veterans Affairs study which identified SVD to be a strong independent predictor of mortality.…”
Section: Discussionsupporting
confidence: 91%
“…Larger studies of the Mitroflow prosthesis have raised concerns regarding its durability due to the lack of anticalcification treatment leading to early valve degeneration. 34 With regard to durability of the Trifecta prosthesis, several studies have reported an excellent freedom from reoperation at the 5-year follow-up. 21,35 Despite satisfactory validation of safety and excellent hemodynamic performance, the Trifecta valve appears to be prone to early structural failure due to cusp tear.…”
Section: Reintervention Due To Svdmentioning
confidence: 99%
“…However, the mechanisms of SVD remain unclear, although mechanical stress [ 7 ], inflammation [ 8 ], and an immune response to xenoantigens in BHVs [ 9 , 10 ] have been proposed to nonexclusively contribute as the initial triggers. The absence of anticalcification treatment [ 6 , 11 , 12 ] or the presence of prosthesis–patient mismatch [ 11 ] may lead to calcification of the leaflets and to SVD, and the wide use of glutaraldehyde as a fixative of the BHV leaflets does not prevent SVD. Furthermore, current valve processing does not eliminate valve immunogenicity, as suggested by the substantial amounts of galactose α1,3-galactose (αGal) [ 13 ] and N -glycolylneuraminic acid (Neu5Gc) [ 14 ] residues in BHVs even after glutaraldehyde fixation and by the swine major histocompatibility antigens (SLA-II) expressed in porcine valves after glutaraldehyde fixation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%